Evaluation of the nurse-assisted eHealth intervention 'eHealth@Hospital-2-Home' on self-care by patients with heart failure and colorectal cancer post-hospital discharge: protocol for a randomised controlled trial - Marianne Storm; Ingvild Margreta Morken; Rosalynn C. Austin; Oda Nordfonn; Hege Bjøkne Wathne; Kristin Hjorthaug Urstad; Bjørg Karlsen; Ingvild Dalen; Kari Hanne Gjeilo; Alison Richardson; Glyn Elwyn; Edvin Bru; et al. (BMC, 2024)
Abstract Background Patients with heart failure (HF) and colorectal cancer (CRC) are prone to comorbidity, a high rate of readmission, and complex healthcare needs. Self-care for people with HF and CRC after hospitalisation can be challenging, and patients may leave the hospital unprepared to self-manage their disease at home. eHealth solutions may be a beneficial tool to engage patients in self-care. Methods A randomised controlled trial with an embedded evaluation of intervention engagement and cost-effectiveness will be conducted to investigate the effect of eHealth intervention after hospital discharge on the self-efficacy of self-care. Eligible patients with HF or CRC will be recruited before discharge from two Norwegian university hospitals. The intervention group will use a nurse-assisted intervention-eHealth@Hospital-2-Home-for six weeks. The intervention includes remote monitoring of vital signs; patients' self-reports of symptoms, health and well-being; secure messaging between patients and hospital-based nurse navigators; and access to specific HF and CRC health-related information. The control group will receive routine care. Data collection will take place before the intervention (baseline), at the end of the intervention (Post-1), and at six months (Post-2). The primary outcome will be self-efficacy in self-care. The secondary outcomes will include measures of burden of treatment, health-related quality of life and 30- and 90-day readmissions. Sub-study analyses are planned in the HF patient population with primary outcomes of self-care behaviour and secondary outcomes of medication adherence, and readmission at 30 days, 90 days and 6 months. Patients' and nurse navigators' engagement and experiences with the eHealth intervention and cost-effectiveness will be investigated. Data will be analysed according to intention-to-treat principles. Qualitative data will be analysed using thematic analysis. Discussion This protocol will examine the effects of the eHealth@ Hospital-2-Home intervention on self-care in two prevalent patient groups, HF and CRC. It will allow the exploration of a generic framework for an eHealth intervention after hospital discharge, which could be adapted to other patient groups, upscaled, and implemented into clinical practice. Trial registration Clinical trials.gov (ID 301472).